Is there reciprocity in preferential trade agreements on services? - Juan Marchetti; Martin Roy; Laura Zoratto (World Trade Organization (WTO), 2012)
Are market access commitments on services in Preferential Trade Agreements (PTAs) reciprocal or simply unilateral? If reciprocal, do concessions granted in services depend on concessions received from the trading partner in other services or in non-services areas as well? In this paper we investigate the presence of reciprocity in bilateral services agreements, by sub-sector, mode of supply and type of agreement (North-North, South-North, South-South). To do so, we use a database of concessions given and received by 36 WTO Members in 40 services PTAs. Results reveal the presence of reciprocity at the product (sub-sector) level and across economic sectors (i.e., preferences in services trade in exchange for preferences received in goods trade). Reciprocity is stronger in agreements between developed countries. The findings provide insights into motivations for services PTAs, but also the multilateral negotiations. Indeed, the negotiation of services PTAs provides an incentive to withhold services offers in the Doha Round in order to extract more - reciprocal - concessions at a bilateral level. The existence of reciprocity on a sectoral basis may also hold lessons on optimal ways to improve the multilateral negotiating process.
Keywords: F13; F15; F19; F53; 330; Services; Preferential Trade Agreements; reciprocity; WTO; GATS; Handelspräferenzen; Internationaler Dienstleistungsverkehr; GATS; Internationaler Dienstleistungsverkehr; Handelspräferenzen; WTO-Regeln; GATS